2021
DOI: 10.3390/cancers13071563
|View full text |Cite
|
Sign up to set email alerts
|

ADAM and ADAMTS Proteins, New Players in the Regulation of Hepatocellular Carcinoma Microenvironment

Abstract: The tumor microenvironment plays a major role in tumor growth, invasion and resistance to chemotherapy, however understanding how all actors from microenvironment interact together remains a complex issue. The tumor microenvironment is classically represented as three closely connected components including the stromal cells such as immune cells, fibroblasts, adipocytes and endothelial cells, the extracellular matrix (ECM) and the cytokine/growth factors. Within this space, proteins of the adamalysin family (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 150 publications
(72 reference statements)
0
20
0
Order By: Relevance
“…This switch in HSCs differentiation was mediated by ADAM proteases, and different molecular mechanisms have been reported related to ADAM-mediated EMT in the liver [ 87 , 88 ]. ADAM17 performs its role in promoting EMT of HCC through the activation of the Notch signalling pathway, which occurs after Notch proteolytic cleavage and active Notch intracellular domain (NICD) release [ 89 ]. Recent discoveries report that the pro-EMT effects of ADAM17 were antagonised by specific micro-RNA whose anti-EMT effects determined a decreased expression of mesenchymal markers ( N -cadherin and Vimentin) and of pro-EMT transcription factors (ZEB1, SNAIL and TWIST), with a concomitant increased expression of epithelial marker E-cadherin [ 90 ].…”
Section: Mechanism Of Adam17 Signals Modulation In Fibrotic Diseases and Cancermentioning
confidence: 99%
“…This switch in HSCs differentiation was mediated by ADAM proteases, and different molecular mechanisms have been reported related to ADAM-mediated EMT in the liver [ 87 , 88 ]. ADAM17 performs its role in promoting EMT of HCC through the activation of the Notch signalling pathway, which occurs after Notch proteolytic cleavage and active Notch intracellular domain (NICD) release [ 89 ]. Recent discoveries report that the pro-EMT effects of ADAM17 were antagonised by specific micro-RNA whose anti-EMT effects determined a decreased expression of mesenchymal markers ( N -cadherin and Vimentin) and of pro-EMT transcription factors (ZEB1, SNAIL and TWIST), with a concomitant increased expression of epithelial marker E-cadherin [ 90 ].…”
Section: Mechanism Of Adam17 Signals Modulation In Fibrotic Diseases and Cancermentioning
confidence: 99%
“…The over-expression of these ADAMs predicted poor prognosis in HCC. ADAM18, ADAM21 and ADAM32 were recently associated with HCC invasion (22,26). Conversity, low expression of ADAMTS5 and ADAMTS8 predicted poor prognosis and inhibited the progression of tumor in HCC cells (22,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified two new members of ADAMTSL proteins such as ADAMTSL-6alpha and -6beta, which were association with fibrillin-1-rich microfibrils in elastic connective tissues (12). Furthermore, recent studies demonstrated that adamalysin family (consisting of ADAM, ADAMTS, ADAMTSL) were associated with TME by regulating the inflammatory response and the epithelial-mesenchymal transition in hepatocellular carcinoma (22). The host ADAM28-deficient was correlated with a decreased lung infiltration by CD8+ T lymphocytes, suggesting ADAM28 involved in T cell mobilization and TME regulation (23).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations